Consumer identification with store brands: Differences between consumers according to their brand loyalty - Natalia Rubio Benito; Nieves Villase\~nor; Javier Oubi\~na (BRQ Business Research Quarterly, 2015)
Retail management of store brands (SBs) has focused on achieving positioning in value and creating associations of smart or expert shopping. The result is that value-conscious consumers and market mavens are the main targets of these brands. This study proposes and contrasts empirically a theoretical model of the effect of market mavenism and value consciousness on consumer identification with SBs. We also perform a multi-group analysis based on the consumer tendency to be loyal to the brands he or she buys. Consumers who are loyal to brands are very attractive segments for firms, due to the potential benefits these consumers represent in the long term, whereas consumers with little loyalty to brands can be an attractive segment for potential benefits in the short term. The results obtained in this study show differences between these two groups. For consumers who are loyal to brands, the results stress strong identification with the SB among the most value-conscious consumers, due fundamentally to their greater disagreement with the greater functional risk of these brands as compared to manufacturer brands and due to their greater conviction of the better price-quality ratio of SBs. In consumers with little brand loyalty, we find identification with the SB among the consumers with the greatest market mavenism, as a result of their greater perception of smart or expert shopping for these brands. Significant implications for management are derived from this study."
Keywords: 650; Store brand; Market mavenism; Value consciousness; Perceived value; Brand identification